2009
DOI: 10.1039/b813982b
|View full text |Cite
|
Sign up to set email alerts
|

Modifications induced by pretreatments on Au/SBA-15 and their influence on the catalytic activity for low temperature CO oxidation

Abstract: SBA-15 functionalization with mercaptopropyltrimethoxysilane has been used to prepare supported gold catalysts for the low temperature CO oxidation reaction. Supports and catalysts have been characterized by chemical analysis, CHS analysis, XRD, TGA, nitrogen adsorption-desorption at 77 K, TEM, CPMAS NMR, XPS and EPR. Catalytic runs have been carried out at atmospheric pressure and 313-623 K and the influence of diverse thermal treatments of the samples prior to reaction has been investigated. The presence of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(35 citation statements)
references
References 55 publications
2
33
0
Order By: Relevance
“…2a). Results of the literature have shown that the BET surface area and pore volume slightly decreased upon grafting but that the pore diameter remained almost unchanged [30,31].…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…2a). Results of the literature have shown that the BET surface area and pore volume slightly decreased upon grafting but that the pore diameter remained almost unchanged [30,31].…”
Section: Resultsmentioning
confidence: 96%
“…SBA-15 was then functionalized with two different types of molecules: N-trimethoxysilylpropyl-N,N,N-trimethylammonium chloride (TPTAC, ABCR 50 wt.% in MeOH) or mercaptopropyltrimethoxysilane (MPTMS, Aldrich). These two molecules have been successfully used to obtain gold nanoparticles within the pores of SBA-15, with excellent dispersion and average diameter below 5 nm [30,31].…”
Section: Synthesis Of the Catalystsmentioning
confidence: 99%
“…It has been reported that the hydroxyls on the surfaces of silica can be activated by Ag [149] or Pt [150,151]. Electron paramagnetic resonance (EPR) results also showed that there were defects that can help to activate the reactants after the Au/SBA-15 catalysts were reduced under hydrogen atmosphere at high temperatures [121,152]. Thus, irreducible silica might be more than a spectator for the reaction after proper pretreatment (e.g., reduced by H 2 , treated by water, etc.)…”
Section: Active Sites Of the Au/iros For Co Oxidationmentioning
confidence: 86%
“…Rombi et al [61] functionalized SBA-15 with MPS by co-condensation using a TEOS:MPS molar ratio of 10, and after surfactant removal by Soxhlet extraction with a mixture of ethanol and HCl, gold (3%wt) was loaded using HAuCl 4 as precursor. Once the solution became colorless, indicating the deposition of gold on the SBA-15 surface, sodium citrate was poured into the mixture to reduce the Au 3+ to Au + species.…”
Section: Self-assembly Functionalization Of Msm Before Gold Loadingmentioning
confidence: 99%